Faktor-faktor yang Mengakibatkan Perceraian dalam Perkawinan - Matondang, Armansyah (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik Universitas Medan Area, 2014)
This study aims to identify factors that lead to divorce in the Village of Hope Tanah Pinem Dairi. The study population was Muslim communities have been divorced and remarried totaling 120 households. These samples included 30 heads of families who are Muslims and have been divorced and remarried to the sample in this study were randomly (random sampling). The results showed that the factors that lead to divorce in the household in the village of Hope Tanah Pinem Dairi, among others, namely: fakor young age, economic factors, factors not yet have offspring and factors husband often be harsh to be the cause of divorce in the Village of Hope. Happens result of Divorce in the Village of Hope Tanah Pinem Dairi is the loss of filial affection and Loosening of family relationship between the wife and husband